Perlakuan Hukum Terhadap Status Tanah Hak Milik Dalam Akta Notaris Yang Batal Demi Hukum Oleh Putusan Pengadilan - Suwitra, I Gede Dimas Brahmanda; Purwanto, I Wayan Novy (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024), 2024)
The aim of the study/writing of this article is to conduct a study of legal problems in regulating land rental periods, as well as analyzing legal certainty regarding the status of property rights which are the object of agreements in notarial deeds which are null and void by court decisions. This writing study uses normative legal research methods in solving problems, supported by regulations - invitations, conceptual approaches, and case approaches. The results of the study in this article show that Article 1548 of the Civil Code allows land leases of up to 75 years, but the lack of clarity in this regulation creates legal protection and automotive potential. Furthermore, agreements that attempt to transfer land ownership rights to foreigners through leases absolutely violate the Agrarian Law, causing the agreement to be null and void. The principle of lex specialis derogat legi generali is applied, except for the general rules of the Civil Code. As a result, land that violates the law will fall and be controlled by the state in accordance with the UUPA, which emphasizes land ownership rights for the prosperity of the people.